Sandwich ELISA for hemoglobin A2 quantification and identification of β-thalassemia carriers - Surakit Kuntaruk (2018)
Hemoglobin (Hb) A2(α2δ2) is a minor hemoglobin in human red blood cells. An abnormal increase in the level of HbA2is the most significant parameter in the diagnosis of β-thalassemia carriers. In this study, we produced two monoclonal antibodies (mAbs) that specifically react to the δ-globin chain of HbA2. A sandwich type ELISA was developed employing the produced anti-HbA2mAbs. HbA2levels quantified by the developed sandwich ELISA were highly correlated with those obtained from the standard HPLC method (r = 0.934, p < 0.001). HbA2levels determined by the ELISA were 4.4 ± 1.9% in β-thalassemia heterozygotes compared to 1.4 ± 0.8, 1.9 ± 0.8, 1.5 ± 0.8 and 1.5 ± 0.6% in normal subjects, HbE heterozygotes, suspected α-thalassemia heterozygotes and HbE homozygotes, respectively. Using a cut-off value of 2.5%, β-thalassemia heterozygotes could be separated from non-β-thalassemia heterozygotes with the same accuracy as obtained using the standard HPLC method. More importantly, the developed ELISA was able to determine HbA2levels in HbE-bearing individuals which could not be done by the HPLC method. Our results suggest that this sandwich ELISA can be applied for mass screening for β-thalassemia heterozygotes, especially in resource-limited countries, where β-thalassemia is highly prevalent. © 2010 The Japanese Society of Hematology.